2013
DOI: 10.4047/jap.2013.5.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometrically assessing the validity of superior, middle and inferior tragus points on ala-tragus line while establishing the occlusal plane in edentulous patient

Abstract: PURPOSEThe purpose of this study was to decide the most appropriate point on tragus to be used as a reference point at time of marking ala tragus line while establishing occlusal plane.MATERIALS AND METHODSThe data was collected in two groups of subjects: 1) Dentulous 2) Edentulous group having sample size of 30 for each group with equal gender distribution (15 males, 15 females each). Downs analysis was used for base value. Lateral cephalographs were taken for all selected subjects. Three points were marked o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
3
16
1
1
Order By: Relevance
“…The results of this study are in agreement with a study done by van Niekerk et al, 35 and many others including Rostamkhani et al, 46 Sharifi and Rostamkhani, 47 Hindocha et al, 48 Chaturvedi and Thombare, 49 Hartono, 51 and Kumar et al 52 who reported that the occlusal plane was parallel to a line joining the inferior part of the ala and inferior part of the tragus, and that these landmarks should be used to orient occlusal planes in edentulous patients during complete denture fabrication.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study are in agreement with a study done by van Niekerk et al, 35 and many others including Rostamkhani et al, 46 Sharifi and Rostamkhani, 47 Hindocha et al, 48 Chaturvedi and Thombare, 49 Hartono, 51 and Kumar et al 52 who reported that the occlusal plane was parallel to a line joining the inferior part of the ala and inferior part of the tragus, and that these landmarks should be used to orient occlusal planes in edentulous patients during complete denture fabrication.…”
Section: Discussionsupporting
confidence: 93%
“…In the past, research has been carried out by various authors to determine the relationship between the ala‐tragal line and occlusal plane. Some of these studies were cephalometric studies (Rostamkhani et al, Sharifi and Rostamkhani, Hindocha et al, Chaturvedi and Thombare, Al Quran et al), some used the modified Trubyte occlusal plane plate (Hartono) and photography (Kumar et al and Sadr and Sadr), and some used the custom‐made occlusal plane analyzer (Shigli et al, Gupta and Singh).…”
mentioning
confidence: 99%
“…The angular values between the occlusal plane and the ala-tragus line (AT1-OP; AT2-OP; and AT3-OP) are not exactly 0°, both in normal individuals and in people with down syndrome. The results of this study are in accordance with the results of Nayar et al, 9 Kumar et al, 10 Chaturvedi et al, 15 and Dean et al 16 in that there is no angle value right at 0°. The results of this study show that the ala-tragus line, which is the most parallel to the occlusal plane in a normal individual, is the inferior Al-tragus line (AT3).…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with the finding of the previous researches stating that the line from the lower border of the ala nose to the inferior tragus is the most parallel ala-tragus line to the occlusal plane and can be used as a guide to determine the parallelism of the occlusal orientation plane in dentures fabrication. 9,10,15,16 The results of the Venugopalan et al, 11 showed that the occlusal plane in normal individuals with class I and III malocclusions is parallel with the line from the lower border of ala nose to the inferior border of tragus, while the occlusal plane in normal individuals with class II malocclusion is parallel with the line from the lower border of ala nose to the middle border of the tragus. Occlusion classifications in this research were not considered in the research criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation